Effect of fuel nuclide composition on the fuel lifetime of the RITM-200 reactor unit; Annals of Nuclear Energy; Vol. 173 - Belyavsky S. V. Sergey Vladimirovich; Anikin N. A. Nikita Andreevich; Alkhassan S. Samiru; Kudeev S. P. Semen Pavlovich; Nesterov V. N. Vladimir Nikolaevich (2022, 2022)
Title screen